1998
DOI: 10.1074/jbc.273.51.34594
|View full text |Cite
|
Sign up to set email alerts
|

Mitosis-specific Phosphorylation and Subcellular Redistribution of the RIIα Regulatory Subunit of cAMP-dependent Protein Kinase

Abstract: 54 . Whereas RII␣ was associated with the Golgi-centrosomal region during interphase, it was dissociated from its centrosomal localization at metaphaseanaphase transition. Furthermore, particulate RII␣ from HeLa cell extracts was solubilized following incubation with CDK1 in vitro. Our results suggest that at the onset of mitosis, CDK1 phosphorylates RII␣, and this may alter its subcellular localization.Cyclic AMP-dependent protein kinases (PKAs) 1 are present in mammalian tissues as two major isozymes, typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 49 publications
(42 reference statements)
2
36
0
Order By: Relevance
“…cAMP primarily exerts its actions through PKA. When PKA is activated, the catalytic subunit autophosphorylates the regulatory subunit and this may facilitate dissociation and activation of the catalytic subunits (Keryer et al, 1998). To determine whether PKA activation is modulated after TBI, we performed western blot analysis with antibodies to phosphorylated, activated PKA regulatory subunit II.…”
Section: Resultsmentioning
confidence: 99%
“…cAMP primarily exerts its actions through PKA. When PKA is activated, the catalytic subunit autophosphorylates the regulatory subunit and this may facilitate dissociation and activation of the catalytic subunits (Keryer et al, 1998). To determine whether PKA activation is modulated after TBI, we performed western blot analysis with antibodies to phosphorylated, activated PKA regulatory subunit II.…”
Section: Resultsmentioning
confidence: 99%
“…Strikingly, in the presence of U0126, late G 2 cells exhibited linked rather than unlinked Golgi elements, and the number of discrete elements matched control values (Figure 7, A-C, late G 2 ϩ U0126), indicating that MEK1 activity is required for Golgi unlinking in late G 2 . Furthermore, olomoucine II treatment, which induced the expected arrest in late G 2 (Keryer et al, 1998) was also observed in a distinct cell type. Synchronized normal rat kidney (NRK) cells were analyzed using anti-giantin immunostaining, and the G 2 population of cells exhibited a significant increase in unlinked Golgi elements compared with the S-phase population, but this increase was absent if U0126 was added to inhibit MEK activity ( Figure 7D).…”
Section: Mek Promotes Golgi Unlinking Before Prophasementioning
confidence: 99%
“…As expected, the Golgi ribbon was intact in S-phase cells, and green fluorescent protein (GFP)-labeled GalNacT2 rapidly recovered after photobleaching (Figure 6, A, C, and Supplemental Figure S3 movie). To accumulate late G 2 cells, thymidine washout was carried out in the presence of the CDK1 inhibitor olomoucine II (Krystof et al, 2005), which induced the expected arrest just before M phase (Keryer et al, 1998). Importantly, in late G 2 cells the ribbon was significantly fragmented (quantified below), and there was impaired fluorescence recovery even when the photobleaching was carried out on a region in proximity to other Golgi structures ( Figure 6, B and C, and Supplemental Figure S4 movie).…”
Section: Mek Promotes Golgi Unlinking Before Prophasementioning
confidence: 99%
“…Trophoblastic cells fuse in response to treatment with cAMP [7] [19]. Forskolin is often used to induce cAMP level and fusion of trophoblastic cells [19].…”
Section: Expression Of Grp78 Is Upregulated By Forskolin Treatment Inmentioning
confidence: 99%